Investigation on the public bus issues in Kota Kinabalu city - Zulkitti Madisibi; Lillian Gungat; Mohd Azizul Ladin; Nadzirah Jausus (e-VIBS, Faculty of Science and Natural Resources, 2022)
The public bus services play an important role in city. However, the number of public transport users is declining day by day and the public chooses to own and use private vehicles due to its convenience. Consequently, number of vehicles on the road increases which lead to severe road congestion. Hence, this study identifies the issue of public transportation in Kota Kinabalu that deters from the establishment of integrated public transportation system. Data were collected through site observation and survey questionnaire at selected study area and responses from bus users was analyzed using SPSS software. The results show that the public are dissatisfied with the overall quality of public bus services in Kota Kinabalu especially in terms of public bus transfer/interchanges, bus trip schedule, waiting time, walking distance to bus stop, route planning, comfort, the punctuality of bus arrival as well as the overall quality of bus stops. It is found that current public bus service is uncomfortable for older bus user. Apart from that, the quality of public bus differs across line of services where better quality service experienced in areas closer to CBD. In order to make transition into an integrated public bus system, improvement of the overall public bus quality need to takes all these factors into account.